VTA DA neuron excitatory synapses in Shank3 Δex4–9 mouse line. Issue 6 (27th January 2017) - Bariselli, Sebastiano; Bellone, Camilla
Abstract: Several mutations within SHANK3 gene have been identified in Autism Spectrum Disorder patients and several studies have now started to show that those mutations could impact different brain circuits leading to the heterogeneity of the disease. Here we show that, compared to a mouse model lacking SHANK3 proline‐rich containing isoforms, in a mouse model lacking SHANK3 ANK(yrin)‐domain containing isoforms, the excitatory synaptic transmission within the Ventral Tegmental Area is not affected. We discuss about the possibility that different domains of SHANK3 are involved in regulating the synapses in a circuit‐specific manner resulting in different behavioral and synaptic phenotypes. Abstract : VTA DA neuron excitatory synapses in Shank3 Δex 4‐9 mouse line . The ventral tegmental area (VTA) is at the origin of the reward system, from where dopamine‐releasing (DA) neurons send projections to their target structures. DA neuron excitatory inputs undergo a process of maturation through both the removal of GluA2‐lacking AMPARs and the partial exchange of GluN2B for GluN2A subunit of NMDARs (Bellone et al., 2011). We have previously shown that the post‐natal downregulation of the Proline‐rich containing isoforms of SHANK3 interferes with the removal of GluA2‐lacking AMPARs from the maturing synapses (Bariselli, Tzanoulinou et al., 2016). Here, we report that the absence of the SHANK3 Ankirin‐containing isoforms, in the constitutive Shank3 Δex 4‐9 mouse line, allows the maturation of both AMPA and NMDA transmission. These results point to an isoform‐specific and time‐dependent effect of SHANK3 genetic removal on synaptic maturation of VTA DA neuron excitatory inputs.